1988
DOI: 10.1128/jb.170.1.308-315.1988
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an Escherichia coli K-12 mutant deficient in glutaredoxin

Abstract: Mutants of Escherichia coli K-12 deficient in glutaredoxin were isolated and partially characterized. The mutants have detectable but significantly reduced glutaredoxin activity in assays of whole cells made permeable with ether as well as in assays of crude extracts coupled to ribonucleotide reductase. In vivo, the mutants appear to be deficient in both sulfate and ribonucleotide reduction, suggesting that in vivo glutaredoxin is the preferred cofactor for ribonucleotide reductase and adenosine 3'-phosphate 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…None of these strains required cysteine or glutathione to grow in NZ-amine-A medium. Similar findings have been reported for trxB grxA and trxA grxA mutants and were attributed to the inability of these strains to reduce PAPS reductase, an enzyme that is required for growth when sulfate is the only source of sulfur in the medium (32,38,39).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…None of these strains required cysteine or glutathione to grow in NZ-amine-A medium. Similar findings have been reported for trxB grxA and trxA grxA mutants and were attributed to the inability of these strains to reduce PAPS reductase, an enzyme that is required for growth when sulfate is the only source of sulfur in the medium (32,38,39).…”
Section: Resultssupporting
confidence: 84%
“…Previous reports suggested that trxB gor and trxB gshA strains do not exhibit an aerobic growth defect, although the trxB gor strain described was not viable at 42°C (38,49). Suppressor mutations may have been unwittingly selected during the manipulations of these strains.…”
Section: Discussionmentioning
confidence: 88%
“…Genetic and biochemical studies suggest that some GRXs are cofactors for ribonucleotide reductase (5,(31)(32)(33). Indeed, the encoding of both subunits of ribonucleotide reductase by vaccinia virus provides a rationale for the presence of a viral grx.…”
Section: Discussionmentioning
confidence: 99%
“…However, oxidized glutaredoxin is reduced directly by cellular glutathione, and the resulting GSSG is, in turn, reduced by NADPH via the glutathione reductase reaction (69). Recent experiments have suggested that glutaredoxin may support most of the ribonucleotide reduction under normal conditions in E. cofi (97).…”
Section: B Cellular Redox Buffersmentioning
confidence: 99%